Functional composite current collector, preparation method thereof and fluorine ion battery
By introducing a conductive agent with negative charge functional groups into the functional composite fluid of the fluoride ion battery, the problem of poor circulation performance of traditional fluoride ion batteries is solved, and higher circulation stability and safety performance are achieved.
Patent Information
- Application Number
- CN202510352774.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The poor circulation performance of traditional fluoride ion batteries limits their application in the field of energy storage.
A functional composite fluid collecting fluid is provided, including a support layer, a conductive layer and a primer layer. The primer layer includes a first binder and a conductive agent. The functional groups on the surface of the conductive agent are negatively charged, which can generate electrostatic repulsion on the fluorine ions, reduce the migration of the fluorine ions to the interface between the functional composite fluid collector and the active material layer, thereby improving the adhesion of the active material layer.
By improving the adhesion between the active material layer and the functional composite fluid collecting fluid, the cycle stability of the fluoride ion battery is significantly improved and the mechanical and safety performance of the battery is enhanced.
Smart Images

Figure CN119890319A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a functional composite current collector and a preparation method thereof, and a fluoride ion battery. Background Art
[0002] Fluoride ion battery is a kind of battery that utilizes fluoride ions (F - ) is a secondary battery that shuttles carriers between the positive and negative electrodes. It is a "rocking chair battery" with a working principle similar to that of lithium-ion batteries. Fluorine is the most electronegative element. Fluoride ions have excellent oxidation resistance and can match high-voltage positive electrode materials. Fluorine reserves are abundant and the annual output is high, which can effectively control battery costs. Fluoride ion batteries will not have dendrite growth problems during the charge and discharge cycle, and have good safety performance. They are expected to challenge lithium-ion batteries in the field of energy storage. However, the poor cycle performance of traditional fluoride ion batteries limits their application in the field of energy storage. Summary of the invention
[0003] Based on this, it is necessary to provide a functional composite current collector and a preparation method thereof and a fluoride ion battery to solve the problem of poor cycle performance of traditional fluoride ion batteries.
[0004] The above-mentioned purpose of the present application is achieved through the following technical solutions:
[0005] In a first aspect of the present application, a functional composite current collector is provided, comprising a support layer, a conductive layer disposed on at least one surface of the support layer, and a primer layer disposed on a surface of the conductive layer away from the support layer;
[0006] The support layer includes a polymer base film and a toughening agent dispersed in the polymer base film;
[0007] The primer layer includes a first binder and a conductive agent dispersed in the first binder, the functional groups on the surface of the conductive agent carry negative charges in the solution, and the functional groups include one or more of hydroxyl, carboxyl, halogen and oxygen-metal bond.
[0008] In some embodiments, the conductive agent includes one or more of carboxylated carbon nanotubes, polyhydroxyfullerenes, and MXene materials; the MXene material includes Ti3C2T x 、Ti2CT x 、Ti3CNT x 、Ta4C3T x 、V2CT x 、V3C2T x 、Mo2CT x and Mo2TiC2T xOne or more of, wherein T includes one or more of -OH, -F and -O, and x>0.
[0009] In some embodiments, the first binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, hydrogenated nitrile rubber, polyvinyl alcohol, polymethacrylic acid, polymethyl methacrylate, polyacrylic acid, sodium polyacrylate, polyacrylamide, sodium alginate, sodium carboxymethyl cellulose and carboxymethyl chitosan.
[0010] In some embodiments, the mass ratio of the first binder to the conductive agent is 1:(0.1-4).
[0011] In some embodiments, the base coating further includes a dispersant, and the dispersant includes one or more of polyvinyl pyrrolidone, sodium polyacrylate, sodium lignin sulfonate, and sodium polystyrene sulfonate, and the mass ratio of the first binder to the dispersant is 1: (0.1~1).
[0012] In some embodiments, the primer layer has a thickness of 0.5 μm to 3 μm.
[0013] In some embodiments, the surface roughness of the primer layer is 100 nm to 800 nm.
[0014] In some embodiments, the peel strength of the primer layer is 14N / 25mm~30N / 25mm.
[0015] In some embodiments, the toughening agent includes bacterial cellulose, a polydopamine layer coated on the bacterial cellulose, and an amino-modified layer grafted on the polydopamine layer.
[0016] In some embodiments, the method for preparing the toughening agent comprises the following steps:
[0017] mixing bacterial cellulose, dopamine and a buffer solution, allowing the dopamine to self-polymerize to form a polydopamine layer covering the bacterial cellulose, to obtain an intermediate;
[0018] The intermediate is dispersed in a mixed solution containing an aminating agent, and the aminating agent is grafted onto the polydopamine layer to form the amino-modified layer, thereby obtaining the toughening agent.
[0019] In some embodiments, the mass ratio of the bacterial cellulose, the dopamine and the amination agent is 1:(0.5-2):(0.5-5).
[0020] In some embodiments, the bacterial cellulose has a diameter of 10 nm to 200 nm, a length of 100 nm to 2000 nm, and an aspect ratio of 0.5 to 200.
[0021] In some embodiments, the amination agent includes one or more of ethylenediamine, histamine, polyethyleneimine, and hexadecyltrimethylammonium bromide.
[0022] In some embodiments, the mass ratio of the polymer base film to the toughening agent is 100:(1-10).
[0023] In some embodiments, the thickness of the support layer is 4 μm to 8 μm.
[0024] In some embodiments, the functional composite current collector further comprises a first safety coating, wherein the first safety coating is disposed between the support layer and the conductive layer;
[0025] The first safety coating comprises a second binder and a phase change material in a mass ratio of (2-5):(95-98), wherein the melting point of the phase change material is 85°C-120°C; or
[0026] The first safety coating includes a second binder and microcapsules in a mass ratio of (2~10):(90~98), the microcapsules include a flame retardant and a phase change material coated on the flame retardant, the mass ratio of the flame retardant to the phase change material is 1:(1.2~40), and the melting point of the phase change material is 85℃~120℃.
[0027] In a second aspect of the present application, a method for preparing the functional composite current collector as described above is provided, comprising the following steps:
[0028] The polymer resin and the toughening agent are melt-blended and the obtained mixture is subjected to film-forming treatment, wherein the polymer resin forms a polymer base film and the toughening agent is dispersed in the polymer base film to obtain a support layer;
[0029] forming a conductive layer on at least one surface of the support layer;
[0030] A primer slurry containing a first binder and a conductive agent is applied onto the conductive layer and dried to form a primer layer.
[0031] In a third aspect of the present application, a fluoride ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the positive electrode sheet and / or the negative electrode sheet comprises the functional composite current collector as described above, or comprises a functional composite current collector prepared by the preparation method of the functional composite current collector as described above.
[0032] In some embodiments, the isolation film includes a base film and a second safety coating layer coated on at least one surface of the base film;
[0033] The second safety coating comprises a second binder and a phase change material in a mass ratio of (2-5):(95-98), wherein the melting point of the phase change material is 85°C-120°C; or
[0034] The second safety coating includes a second binder and microcapsules in a mass ratio of (2~10):(90~98), the microcapsules include a flame retardant and a phase change material coated on the flame retardant, the mass ratio of the flame retardant to the phase change material is 1:(1.2~40), and the melting point of the phase change material is 85℃~120℃.
[0035] This application has at least the following beneficial effects:
[0036] The functional composite current collector provided by the present application includes a support layer, a conductive layer and a bottom coating layer. Among them, the bottom coating layer includes a first binder and a conductive agent, and the functional groups on the surface of the conductive agent carry a negative charge in the solution environment, which can generate electrostatic repulsion for fluoride ions, prevent fluoride ions from migrating to the interface between the functional composite current collector and the active material layer, reduce the probability of active materials at the interface participating in the conversion reaction, and the probability of stress strain at the interface is reduced, thereby improving the adhesion of the active material layer on the functional composite current collector, thereby improving the cycle performance of the fluoride ion battery. Compared with the traditional composite current collector, the bottom coating layer has a high surface roughness and good bonding performance, which effectively enhances the peeling strength between the active material layer and the functional composite current collector, which is beneficial to prevent the detachment or peeling of the active material layer. At the same time, the support layer includes a polymer base film and a toughening agent, which can enhance the tensile strength, elongation at break and toughness of the support layer, improve the mechanical properties of the functional composite current collector, and help improve the cycle performance of the battery. Therefore, the functional composite current collector provided by the present application has high structural stability and strong adhesion to the active material layer, which can significantly improve the cycle stability of the fluoride ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0038] Figure 1 Schematic diagram of the structure of a functional composite current collector in some embodiments;
[0039] Figure 2 Schematic diagrams of the structures of functional composite current collectors in other embodiments;
[0040] Figure 3is a schematic diagram of a process for preparing a functional composite current collector in some embodiments;
[0041] Figure 4 Schematic diagram of the structure of the isolation membrane in some embodiments.
[0042] Reference numerals: 11, support layer; 12, conductive layer; 13, primer layer; 14, first security coating layer; 21, base film; 22, second security coating layer. DETAILED DESCRIPTION
[0043] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0045] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. The meaning of "one or more" is more than one, such as one, two and more than two. The meaning of "multiple" or "several" is at least two, such as two, three, etc., and the meaning of "multi-layer" is at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0046] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.
[0047] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0048] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.
[0049] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0050] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.
[0051] The pole piece is an important component of the fluoride ion battery. The pole piece includes a current collector and an active material layer disposed on at least one surface of the current collector. Among them, the active material layer of the fluoride ion battery usually adopts a conversion electrode active material. For example, when a metal fluoride (such as CuF2) is used as the positive electrode active material, during discharge, the fluoride ions in the metal fluoride are released and reduced to a metal element; during charging, the metal element and the fluoride ions combine to regenerate the metal fluoride. Therefore, the chemical composition and phase structure of the conversion electrode active material will change during the charge and discharge process, accompanied by a significant volume change, so that the interface between the active material layer and the current collector produces obvious stress and strain, and even causes the active material layer to fall off the current collector as a whole, resulting in the deterioration of the cycle performance of the fluoride ion battery. In addition, the current collector can be a metal foil or a composite current collector. Compared with a metal foil, at the same thickness, the composite current collector is lighter, and the energy density of the assembled fluoride ion battery is higher. However, the poor mechanical properties of the composite current collector will also affect the cycle performance of the fluoride ion battery.
[0052] Based on this, in the first aspect of the present application, a functional composite current collector is provided to solve the problem of poor cycle performance of traditional fluoride ion batteries.
[0053] In some embodiments, Figure 1As shown, the functional composite current collector includes a support layer 11 , a conductive layer 12 disposed on both surfaces of the support layer 11 , and a primer layer 13 disposed on a surface of the conductive layer 12 away from the support layer 11 .
[0054] The support layer 11 includes a polymer base film and a toughening agent dispersed in the polymer base film;
[0055] The primer layer 13 includes a first binder and a conductive agent dispersed in the first binder. The functional groups on the surface of the conductive agent carry negative charges in the solution. The functional groups include one or more of hydroxyl groups, carboxyl groups, halogen groups and oxygen atoms.
[0056] The functional composite current collector provided in the present application includes a support layer 11, a conductive layer 12 and a bottom coating layer 13. Among them, the bottom coating layer 13 includes a first binder and a conductive agent, and the functional groups on the surface of the conductive agent carry a negative charge in the solution environment, which can generate electrostatic repulsion for fluoride ions, prevent fluoride ions from migrating to the interface between the functional composite current collector and the active material layer, reduce the probability of the active material at the interface participating in the conversion reaction and undergoing a significant volume change, and the probability of stress and strain at the interface is reduced accordingly, thereby improving the adhesion of the active material layer on the functional composite current collector, thereby improving the cycle performance of the fluoride ion battery. Compared with the traditional composite current collector, the bottom coating layer 13 has a high surface roughness and good bonding performance, which effectively enhances the peeling strength between the active material layer and the functional composite current collector, and is conducive to preventing the active material layer from detaching or peeling off. At the same time, the support layer 11 includes a polymer base film and a toughening agent, which can enhance the tensile strength, elongation at break and toughness of the support layer 11, improve the mechanical properties of the functional composite current collector, and is conducive to improving the cycle performance of the battery. Therefore, the functional composite current collector provided by the present application has high structural stability and strong adhesion to the active material layer, and can significantly improve the cycle stability of the fluoride ion battery.
[0057] The following is some description about the support layer 11 .
[0058] In some embodiments, the material of the polymer-based film includes one or more of polyethylene (PE), polypropylene (PP), polyimide (PI), polyvinyl chloride (PVC), polystyrene (PS), polyvinyl alcohol (PVA), polyethylene terephthalate (PET), and polybutylene terephthalate (PBT). Further, the material of the polymer-based film includes one or more of polypropylene (PP), polyimide (PI), and polyethylene terephthalate (PET).
[0059] In some embodiments, the toughening agent includes bacterial cellulose, a polydopamine layer coated on the bacterial cellulose, and an amino-modified layer grafted on the polydopamine layer.
[0060] In some embodiments, the method for preparing the toughening agent comprises the following steps:
[0061] S110: mixing bacterial cellulose, dopamine and a buffer solution, allowing dopamine to self-polymerize to form a polydopamine layer covering the bacterial cellulose, to obtain an intermediate;
[0062] S120: dispersing the intermediate in a mixed solution containing an aminating agent, so that the aminating agent is grafted onto the polydopamine layer to form an amino-modified layer, thereby obtaining a toughening agent.
[0063] In the present application, the preparation mechanism of the toughening agent is as follows: dopamine (DA) contains amino groups and catechol functional groups (or catechol functional groups), which can spontaneously polymerize to form polydopamine (PDA) under neutral or alkaline conditions. PDA is coated on the surface of bacterial cellulose to form a polydopamine layer, which provides abundant functional groups and active sites, and can undergo covalent cross-linking reaction with amino groups (or imino groups) in the amination reagent through Michael addition, thereby forming an amino-modified layer. In this way, the toughening agent surface contains a large number of amino groups, which helps to enhance the bonding force between it and the polymer base film, thereby enhancing the toughening effect of the support layer 11.
[0064] In some embodiments, the mass ratio of bacterial cellulose, dopamine and amination agent is 1: (1-2): (1-5). As an example, the mass ratio of bacterial cellulose and dopamine includes but is not limited to 1: 1, 1: 1.2, 1: 1.4, 1: 1.6, 1: 1.8 or 1: 2, and the mass ratio of bacterial cellulose and amination agent includes but is not limited to 1: 1, 1: 2, 1: 3, 1: 4 or 1: 5. Further, the mass ratio of bacterial cellulose, dopamine and amination agent is 1: 1: 1.
[0065] In some embodiments, the diameter of the bacterial cellulose is 10 nm to 200 nm, the length is 100 nm to 2000 nm, and the aspect ratio is 0.5 to 200. As an example, the diameter of the bacterial cellulose includes but is not limited to 10 nm, 20 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm or 200 nm, the length includes but is not limited to 100 nm, 200 nm, 500 nm, 800 nm, 1000 nm, 1200 nm, 1500 nm, 1800 nm or 2000 nm, and the aspect ratio includes but is not limited to 0.5, 1, 5, 10, 20, 50, 80, 100, 120, 150, 180 or 200.
[0066] In some embodiments, the buffer solution includes a tris-hydroxymethylaminomethane hydrochloride buffer solution, i.e., a Tris-HCl buffer solution. The pH of the Tris-HCl buffer solution is 7 to 9, and the concentration is 10 mM to 20 mM. Furthermore, the pH of the Tris-HCl buffer solution is 8.5, and the concentration is 10 mM.
[0067] In some embodiments, the mass fraction of bacterial cellulose in the buffer solution is 0.1% to 1%. Further, the mass fraction of bacterial cellulose in the buffer solution is 0.5%.
[0068] In some embodiments, the mass fraction of dopamine in the buffer solution is 0.1% to 1%. Further, the mass fraction of dopamine in the buffer solution is 0.5%.
[0069] In some embodiments, in step S110, mixing bacterial cellulose, dopamine and a buffer solution comprises the following steps: dispersing bacterial cellulose in a buffer solution, and adding dopamine under ultrasonic conditions.
[0070] In some embodiments, in step S110, dopamine is self-polymerized to form a polydopamine layer coating bacterial cellulose, comprising the following steps: continuous stirring for 12h~36h at pH=7~9, temperature of 10℃~40℃, and rotation speed of 100rpm~1000rpm.
[0071] In some embodiments, in step S110, after the self-polymerization reaction, the following step is further included: removing residual dopamine and unstable polydopamine on the surface of the intermediate by water washing.
[0072] In some embodiments, the amination agent includes one or more of ethylenediamine (EDA), histamine (1H-imidazole-4-ethylamine), polyethyleneimine (PEI) and hexadecyltrimethylammonium bromide (CTAB). Further, the amination agent is polyethyleneimine (PEI).
[0073] In some embodiments, the mass fraction of the amination agent in the mixed solution is 0.1% to 1%, including but not limited to 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8% or 1%.
[0074] In some embodiments, the amination reagent is grafted onto the polydopamine layer to form an amino-modified layer, comprising the following steps: stirring continuously for 6 h to 24 h at a temperature of 40° C. to 60° C. and a rotation speed of 100 rpm to 1000 rpm.
[0075] In some embodiments, in step S120, after the grafting reaction, the following step is further included: removing the unreacted amination reagent on the surface of the toughening agent by water washing.
[0076] In some embodiments, the mass ratio of the polymer base film to the toughening agent is 100: (1-10), including but not limited to 100: 1, 100: 2, 100: 3, 100: 4, 100: 5, 100: 6, 100: 7, 100: 8, 100: 9 or 100: 10. Further, the mass ratio of the polymer base film to the toughening agent is 100: (1-4).
[0077] Therefore, adding an appropriate amount of toughening agent to the support layer 11 can fully exert its toughening effect, enabling it to buffer stress and maintain structural stability during battery preparation and operation, thereby providing a guarantee for the stable performance of the battery.
[0078] In some embodiments, the thickness of the support layer 11 is 4 μm to 8 μm, including but not limited to 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm or 8 μm.
[0079] The following is some description about the conductive layer 12 .
[0080] In this application, if Figure 1 As shown, the support layer 11 has two surfaces opposite to each other in its thickness direction, and the conductive layer 12 is disposed on the two opposite surfaces of the support layer 11. However, the present application is not limited thereto, and in some other embodiments, the conductive layer 12 may also be disposed on any one of the two opposite surfaces of the support layer 11.
[0081] In some embodiments, the material of the conductive layer 12 includes one or more of stainless steel, copper (Cu), nickel (Ni) and aluminum (Al).
[0082] If the functional composite current collector is applied to the positive electrode plate, the material of the conductive layer 12 can be aluminum (Al).
[0083] If the functional composite current collector is applied to the negative electrode plate, the material of the conductive layer 12 can be copper (Cu), nickel (Ni) or stainless steel.
[0084] In some embodiments, the thickness of the conductive layer 12 is 0.5 μm to 4 μm, including but not limited to 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm or 4 μm.
[0085] The following is some description about the primer layer 13 .
[0086] In some embodiments, in the primer layer 13, the functional groups on the surface of the conductive agent carry a negative charge in the solution, and the functional groups include one or more of a hydroxyl group (-OH), a carboxyl group (-COOH), a halogen (-F, -Cl, -Br or -I) and an oxygen-metal bond (-O).
[0087] It is understood that hydroxyl (-OH) and carboxyl (-COOH) groups can be negatively charged (-O - and -COO - ). Halogens (such as -F) have high electronegativity, which can make the surface of the conductive agent have a negative charge. Oxygen-metal bonds (-O, or MO bonds) are stable chemical bonds formed by oxygen atoms combining with surface metal atoms through substitution or adsorption. The high electronegativity of oxygen atoms makes the surface of MXene materials have a certain negative charge, especially in a solution environment.
[0088] In the present application, the method for testing the surface charge of the conductive agent can be a Zeta potential test method. The solution environment for the test can be water or an organic solvent, and the test sample is dispersed in deionized water at a mass fraction of 0.01% to 0.1% to obtain a suspension, and then tested using a Zeta potential meter.
[0089] In some embodiments, in the base coating layer 13, the conductive agent includes one or more of carboxylated carbon nanotubes, polyhydroxyfullerenes, and MXene materials.
[0090] In the present application, the surface of the carboxylated carbon nanotubes contains a large number of carboxyl groups, the surface of the polyhydroxyfullerene contains a large number of hydroxyl groups, and the surface of the MXene material contains a large number of active functional groups, such as -OH, -F or -O. These functional groups carry negative charges through deprotonation or adsorption in a solution environment, which can provide strong electrostatic repulsion, prevent fluoride ions from migrating to the interface between the functional composite current collector and the active material layer, and effectively improve the adhesion between the active material layer and the functional composite current collector.
[0091] In some embodiments, the molecular formula of the MXene material is M n+1 X n T x .
[0092] Wherein, n=1, 2, 3; M represents a transition metal element, M includes one or more of Ti, Ta, Mo, V, Sr and Zr; X represents one or more of carbon and nitrogen; T represents a surface active functional group, T includes one or more of -OH, -F and -O, x represents the number of T, x>0.
[0093] In some embodiments, the MXene material includes Ti3C2Tx 、Ti2CT x 、Ti3CNT x 、Ta4C3T x 、V2CT x 、V3C2T x 、Mo2CT x and Mo2TiC2T x One or more of .
[0094] In some embodiments, the MXene material includes one or more of a multilayer MXene material and a single layer MXene material. The thickness of the multilayer MXene material is 5 μm to 50 μm, and the thickness of the single layer MXene material is 0.5 nm to 5 nm.
[0095] In some embodiments, the method for preparing MXene materials comprises the following steps: placing a MAX precursor in a liquid containing hydrogen ions (H + ) and fluoride ions (F - ) in an etching solution for etching reaction and purification treatment to prepare MXene materials.
[0096] In some embodiments, the MAX precursor includes one or more of Ti3AlC2, Ti2AlC, Ti3AlCN, Ta4AlC3, V2AlC, V3AlC2, Mo2AlC, and Mo2TiAlC2.
[0097] In some embodiments, the etching solution contains one or more of HF, HCl and fluoride salts, wherein the fluoride salts include one or more of lithium fluoride (LiF), sodium fluoride (NaF), potassium fluoride (KF), aluminum fluoride (AlF3), and ammonium fluoride (NH4F).
[0098] In some embodiments, the etching solution is an HF solution, and the concentration of HF is 6 mol / L to 12 mol / L, including but not limited to 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L or 12 mol / L.
[0099] In some embodiments, the etching solution is a mixed solution containing HCl and a fluoride salt, wherein the molar ratio of HCl to the fluoride salt is 1:(0.1-0.5), including but not limited to 1:0.1, 1:0.2, 1:0.3, 1:0.4 or 1:0.5. The fluoride salt can be selected from one or more of LiF, NaF and KF.
[0100] In some embodiments, the volume mass ratio of the etching solution to the MAX precursor is 10 mL / g to 20 mL / g, including but not limited to 10 mL / g, 12 mL / g, 14 mL / g, 16 mL / g, 18 mL / g or 20 mL / g.
[0101] In some embodiments, the etching reaction includes the following steps: etching at 20° C. to 50° C. for 12 h to 48 h. As an example, the temperature of the etching reaction can be 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., or 50° C., and the etching reaction time can be 12 h, 16 h, 20 h, 24 h, 28 h, 32 h, 36 h, 40 h, 44 h, or 48 h.
[0102] In some embodiments, the purification treatment includes the following steps: repeatedly centrifuging and washing the reaction liquid after the etching reaction with HCl solution and deionized water until the pH value of the upper layer liquid after centrifugation is ≥6 to obtain a washing product; dispersing the washing product in deionized water and ultrasonicating it under an inert gas atmosphere to obtain a dispersion; and then high-speed centrifuging and freeze-drying the dispersion to obtain a MXene material.
[0103] In some embodiments, the first binder includes one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR), polyvinyl alcohol (PVA), polymethacrylic acid (PMAA), polymethyl methacrylate (PMMA), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), sodium alginate (SA), sodium carboxymethyl cellulose (CMC) and carboxymethyl chitosan (CMCS).
[0104] If the functional composite current collector is applied to the positive electrode sheet, the first binder can be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), sodium carboxymethyl cellulose (CMC) and carboxymethyl chitosan (CMCS), and can further be selected from SBR and CMC.
[0105] If the functional composite current collector is applied to the negative electrode plate, the first binder can be selected from one or more of polyvinylidene fluoride (PVDF), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR), polytetrafluoroethylene (PTFE) and polyacrylic acid (PAA), and PVDF can be further selected.
[0106] In some embodiments, the mass ratio of the first binder to the conductive agent is 1:(0.1-4), including but not limited to 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4.
[0107] In some embodiments, the base coating 13 further includes a dispersant, and the dispersant includes one or more of polyvinyl pyrrolidone (PVP), sodium polyacrylate (PAAS), sodium lignin sulfonate, and sodium polystyrene sulfonate (PSS). Furthermore, the dispersant is polyvinyl pyrrolidone (PVP).
[0108] In some embodiments, the mass ratio of the first binder to the dispersant is 1:(0.1-1), including but not limited to 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1.
[0109] In some embodiments, the thickness of the primer layer 13 is 0.5 μm to 3 μm, including but not limited to 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.
[0110] In some embodiments, the surface roughness of the primer layer 13 is 100 nm to 800 nm, including but not limited to 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm or 800 nm;
[0111] In some embodiments, the peel strength of the primer layer 13 is 14N / 25mm~30N / 25mm, including but not limited to 14N / 25mm, 16N / 25mm, 18N / 25mm, 20N / 25mm, 22N / 25mm, 24N / 25mm, 26N / 25mm, 28N / 25mm or 30N / 25mm.
[0112] In some embodiments, Figure 2 As shown, the functional composite current collector further includes a first safety coating 14, which is disposed between the support layer 11 and the conductive layer 12. The first safety coating 14 includes a second binder and a phase change material in a mass ratio of (2-5): (95-98), and the melting point of the phase change material is 85°C-120°C. As an example, the mass ratio of the second binder and the phase change material includes but is not limited to 2:98, 3:97, 4:96 or 5:95, and the melting point of the phase change material includes but is not limited to 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C.
[0113] Thus, when the temperature inside the battery rises abnormally to the melting point of the phase change material, the phase change material absorbs heat and melts, causing the conductive layer 12 on the surface of the first safety coating 14 to fall off, thereby suppressing abnormal circuit current and improving battery safety performance. In addition, under normal operating conditions, the first safety coating 14 can also improve the mechanical properties of the functional composite current collector.
[0114] In some embodiments, the second binder includes one or more of polyimide (PI), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR), polyvinyl alcohol (PVA), polymethacrylic acid (PMAA), polymethyl methacrylate (PMMA), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), sodium alginate (SA), sodium carboxymethyl cellulose (CMC) and carboxymethyl chitosan (CMCS), and may further be PVDF or PI.
[0115] In some embodiments, the phase change material includes one or more of paraffin wax, chlorinated paraffin wax, pearlescent wax and stearic acid. Among them, paraffin wax can be selected from high melting point paraffins such as No. 90 paraffin wax (melting point range 85℃~90℃), No. 95 paraffin wax (melting point range 90℃~95℃) and No. 105 paraffin wax (melting point range 100℃~105℃); chlorinated paraffin can be selected from chlorinated paraffin-70 (melting point range 95℃~120℃); pearlescent wax is a high melting point wax, which is usually used to make pearlescent pigments and coatings, has good stability and pearlescent effect, and pearlescent wax with a melting point of 88℃~93℃ can be selected.
[0116] In some other embodiments, the first safety coating 14 may further include a second binder and microcapsules in a mass ratio of (2-10): (90-98), the microcapsules include a flame retardant and a phase change material coated on the flame retardant, the mass ratio of the flame retardant to the phase change material is 1: (1.2-40), and the melting point of the phase change material is 85° C. to 120° C. As an example, the mass ratio of the second binder to the microcapsules is 2:98, 3:97, 4:96, 5:95, 6:94, 7:93, 8:92, 9:91 or 10:90, and the mass ratio of the flame retardant to the phase change material includes but is not limited to 1:1.2, 1:2, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35 or 1:40.
[0117] Therefore, the introduction of flame retardants is conducive to improving the flame retardant properties of batteries, inhibiting exothermic chain reactions, and further improving the safety performance of batteries. At the same time, the phase change material is coated on the surface of the flame retardant to avoid the loss of the flame retardant under normal working conditions and ensure that its flame retardant effect can be stably exerted under abnormal working conditions.
[0118] In some embodiments, the flame retardant includes one or more of 3-thiopheneboronic acid, pentafluoroethoxycyclotriphosphazene, hexaphenoxycyclotriphosphazene, hexachlorotriphosphazene, Li[P(DPC)3], and poly(ethyl phosphate-ethylene glycol) co-oligomer.
[0119] In some embodiments, in the microcapsule, the particle size of the flame retardant is 40 nm to 400 nm, including but not limited to 40 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm or 400 nm.
[0120] In some embodiments, in the microcapsule, the thickness of the phase change material is 400 nm to 1000 nm, including but not limited to 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm or 1000 nm.
[0121] In some embodiments, the thickness of the first safety coating 14 is 0.5µm to 1.5µm, including but not limited to 0.5µm, 0.6µm, 0.7µm, 0.8µm, 0.9µm, 1µm, 1.1µm, 1.2µm, 1.3µm, 1.4µm or 1.5µm.
[0122] In a second aspect of the present application, a method for preparing a functional composite current collector is provided, which is used to prepare the above-mentioned functional composite current collector.
[0123] In some embodiments, Figure 3 As shown, the preparation method of the functional composite current collector comprises the following steps:
[0124] S210: melt-blending the polymer resin and the toughening agent, and performing film-forming treatment on the obtained mixture, wherein the polymer resin forms a polymer base film, and the toughening agent is dispersed in the polymer base film, thereby obtaining a support layer;
[0125] S220: forming a conductive layer on at least one surface of the supporting layer;
[0126] S230: coating a primer slurry containing a first binder and a conductive agent on the conductive layer, and obtaining a primer layer after drying.
[0127] The following is a detailed description of the preparation method of the functional composite current collector in a step-by-step manner.
[0128] S210: melt-blending the polymer resin and the toughening agent, and performing film-forming treatment on the obtained mixture, wherein the polymer resin forms a polymer base film, and the toughening agent is dispersed in the polymer base film to obtain a support layer.
[0129] In some embodiments, the temperature of melt blending is 170°C to 450°C, including but not limited to 170°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C or 450°C.
[0130] In some embodiments, the melt blending time is 0.5 h to 8 h, including but not limited to 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h.
[0131] In some embodiments, the film forming method includes one or more of compression molding, hot pressing molding, autoclave molding, and calendering molding, and hot pressing molding may be further selected.
[0132] In some embodiments, after the film forming process, the following step is further included: increasing the surface roughness of the support layer by plasma etching process, thereby improving the peeling strength between the support layer and other film layers.
[0133] In some embodiments, the plasma etching process includes the following steps: evacuating the vacuum to 5×10 -5 Pa~8×10 - 5 Pa, an inert gas is introduced at a flow rate of 10sccm~100sccm, and plasma etching treatment is performed under the conditions of a working gas pressure of 0.5Pa~5Pa and a working power of 20W~80W; wherein the inert gas includes one or more of helium, neon, argon, krypton and xenon.
[0134] S220: forming a conductive layer on at least one surface of the support layer.
[0135] In some embodiments, the method for preparing the conductive layer includes magnetron sputtering.
[0136] In some embodiments, the method for preparing the conductive layer comprises the following steps: vacuumizing to ≤5×10 -5 Pa, an inert gas is introduced at a flow rate of 50sccm~100sccm, and DC magnetron sputtering coating is performed under the conditions of a sputtering gas pressure of 0.5Pa~5Pa and a sputtering power of 100W~200W to form a conductive layer; wherein the inert gas includes one or more of helium, neon, argon, krypton and xenon.
[0137] S230: coating a primer slurry containing a first binder and a conductive agent on the conductive layer, and obtaining a primer layer after drying.
[0138] In some embodiments, the preparation method of the primer layer includes the following steps: mixing a conductive agent, a dispersant, a first binder and a first solvent to form a primer slurry, applying the primer slurry on the conductive layer, and vacuum drying at 60°C to 80°C for 48h to 72h. The first solvent includes one or more of N-methylpyrrolidone (NMP) and water, and the water can be deionized water, pure water or ultrapure water; the solid content of the primer slurry is 5% to 20%, including but not limited to 5%, 8%, 10%, 12%, 15%, 18% or 20%; the vacuum drying temperature includes but is not limited to 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, and the vacuum drying time includes but is not limited to 48h, 50h, 55h, 60h, 65h, 70h or 72h.
[0139] In some embodiments, after step S210, the following steps are also included: forming a first safety coating layer on at least one surface of the support layer, and sequentially forming a conductive layer and a primer layer on the first safety coating layer.
[0140] In some embodiments, the preparation method of the first safety coating comprises the following steps: mixing a phase change material, a second binder and a second solvent to form a safety slurry, or mixing a safety capsule, a second binder and a second solvent to form a first safety slurry; applying the first safety slurry to at least one surface of the support layer by an extrusion molding method, and vacuum drying at 60°C to 70°C for 12h to 24h to form the first safety coating. Wherein, the second solvent comprises one or more of N-methylpyrrolidone (NMP) and N,N-dimethylformamide (DMF); the solid content of the safety slurry is 5% to 20%, including but not limited to 5%, 8%, 10%, 12%, 15%, 18% or 20%; the vacuum drying temperature includes but is not limited to 60°C, 62°C, 64°C, 66°C, 68°C or 70°C, and the vacuum drying time includes but is not limited to 12h, 14h, 16h, 18h, 20h, 22h or 24h.
[0141] In some embodiments, the preparation method of the safety capsule includes the following steps: heating the phase change material to melt, impregnating the flame retardant into the molten phase change material, coating a layer of phase change material on the surface of the flame retardant by melt impregnation, cooling, solidifying, and crushing to obtain a safety capsule.
[0142] It is understandable that after forming the first safety coating, during the process of preparing the conductive layer by magnetron sputtering, the temperature in the reaction chamber should be controlled below the melting point of the phase change material to avoid loss of the first safety coating.
[0143] In a third aspect of the present application, a fluoride ion battery is provided. In the present application, the fluoride ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the cycle, fluoride ions (F - ) shuttles back and forth between the positive electrode and the negative electrode. The separator is set between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow fluoride ions to pass through. The electrolyte is between the positive electrode and the negative electrode, mainly to conduct fluoride ions.
[0144] In some embodiments, the positive electrode sheet and / or the negative electrode sheet includes the functional composite current collector described above.
[0145] In some embodiments, the positive electrode sheet includes the functional composite current collector as described above and a positive electrode active layer covering at least one surface of the functional composite current collector.
[0146] In some embodiments, the positive electrode active layer includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder, wherein the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder is (80-95): (2.5-10): (2.5-10), and can further be 80:10:10.
[0147] In some embodiments, the positive electrode active material includes metal fluoride and its modified compound. Among them, the metal fluoride includes one or more of CuF2, FeF3, BiF3, LaF3, MgF2, NiF2 and PbF2, and the modified compound of the metal fluoride can be one or more of mixed modification, doping modification and surface coating modification. Further, the positive electrode active material is a composite material of metal fluoride and carbon, and the carbon can be one or more of conductive carbon black, conductive graphite, acetylene black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers.
[0148] In some embodiments, the positive electrode binder includes one or more of polyvinylidene fluoride (PVDF), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR), polytetrafluoroethylene (PTFE) and polyacrylic acid (PAA), and polyvinylidene fluoride (PVDF) may be further selected.
[0149] In some embodiments, the positive electrode conductive agent includes one or more of conductive carbon black, conductive graphite, acetylene black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers, and may further be conductive carbon black (Super-P, SP).
[0150] In some embodiments, the preparation method of the positive electrode sheet includes the following steps: dispersing the positive electrode active material, the positive electrode conductor and the positive electrode binder in a solvent (such as NMP) to prepare a positive electrode slurry; covering the positive electrode slurry on at least one surface of the functional composite current collector, and obtaining the positive electrode sheet after drying, rolling and cutting.
[0151] In some embodiments, the negative electrode sheet includes the functional composite current collector as described above and a negative electrode active layer covering at least one surface of the functional composite current collector.
[0152] In some embodiments, the negative electrode active layer includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder, wherein the mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder is (80-95): (2.5-10): (2.5-10), and can further be 80:10:10.
[0153] In some embodiments, the negative electrode active material includes metal, metal fluoride, metal carbide and modified compounds of each material. The metal includes one or more of Ca, Sn, La, Bi, Mg, Al and Pb; the metal fluoride includes one or more of SnF2 and PbF2; the metal carbide includes Y2C, and the modified compound of each material can be one or more of mixed modification, doping modification and surface coating modification.
[0154] In some embodiments, the negative electrode binder includes one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), sodium carboxymethyl cellulose (CMC), and carboxymethyl chitosan (CMCS).
[0155] In some embodiments, the negative electrode conductive agent includes one or more of conductive carbon black, conductive graphite, acetylene black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers, and may further be carbon nanofibers (CNF).
[0156] In some embodiments, the preparation method of the negative electrode sheet includes the following steps: using a dry mixing method to prepare a negative electrode active material, a negative electrode conductive agent and a negative electrode binder into a negative electrode powder; hot pressing the negative electrode powder on at least one surface of a functional composite current collector, and obtaining a negative electrode sheet after drying, rolling and cutting.
[0157] It is understood that the electrolyte in the fluoride ion battery can be liquid, gel or all-solid.
[0158] In some embodiments, the electrolyte is an electrolyte solution including a fluoride ion salt and an organic solvent, wherein the fluoride ion salt includes one or more of CsF, KF, NaF and KSnF3; and the organic solvent includes one or more of benzyl alcohol (BA), N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO) and ethylene glycol (EG).
[0159] In some embodiments, Figure 4 As shown, the isolation film includes a base film 21 and a second safety coating 22 coated on at least one surface of the base film 21. The base film 21 can be a porous film with good chemical stability and mechanical stability; meanwhile, the base film 21 can be a single-layer film or a multi-layer composite film. When the base film 21 is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions.
[0160] In some embodiments, the material of the base film 21 includes one or more of glass fiber (GF), non-woven fabric, polyethylene (PE), polypropylene (PP) and polyimide (PI).
[0161] In some embodiments, the second safety coating 22 in the isolation film includes a second binder and a phase change material in a mass ratio of (2-5):(95-98), and the melting point of the phase change material is 85°C-120°C.
[0162] In some other embodiments, the second safety coating 22 includes a second binder and microcapsules in a mass ratio of (2~10): (90~98), the microcapsules include a flame retardant and a phase change material coated on the flame retardant, the mass ratio of the flame retardant to the phase change material is 1: (1.2~40), and the melting point of the phase change material is 85℃~120℃.
[0163] It can be understood that the types of the second binder, phase change material and flame retardant in the second safety coating 22 and their related parameters are substantially the same as those of the first safety coating 14 and will not be described in detail herein.
[0164] Adding flame retardants to the electrolyte can improve the safety performance of the battery, but it will change the viscosity of the electrolyte, deteriorate its ion conductivity, and some flame retardants have poor compatibility with electrode active materials, thus affecting the electrochemical performance of the battery. The flame retardant is coated in the phase change material, and the obtained microcapsules are made into a second safety coating 22, and coated on the surface of the base film 21. On the one hand, it can improve the mechanical properties of the isolation membrane and ensure the stability of the electrochemical performance of the battery. On the other hand, when the temperature inside the battery rises abnormally, the flame retardant in the microcapsule is released, which improves the safety performance of the battery and avoids the adverse effects of adding the flame retardant directly to the electrolyte.
[0165] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly through a winding process or a lamination process, and then injected with an electrolyte to form a battery.
[0166] In some embodiments, the fluoride ion battery may include an outer package for encapsulating the electrode assembly and the electrolyte. The outer package of the fluoride ion battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be an aluminum-plastic film, etc.
[0167] It can be understood that the present application has no particular limitation on the shape of the fluoride ion battery, which may be cylindrical, square or any other shape.
[0168] In a fourth aspect, the present application provides an electrical device, which includes the above-mentioned fluoride ion battery.
[0169] It can be understood that the fluoride ion battery can be used as a power source for an electrical device, or as an energy storage unit for an electrical device. Electrical devices may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited thereto.
[0170] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.
[0171] Example 1
[0172] The preparation method of the fluoride ion battery provided in this embodiment is as follows:
[0173] (1) Preparation of toughening agent:
[0174] 0.5% mass fraction of bacterial cellulose (diameter 100nm, length 500nm, aspect ratio 5) was dispersed in Tris-HCl buffer solution (pH=8.5, 10mM), and 0.5% mass fraction of dopamine was added under ultrasonic conditions. The mixture was stirred continuously for 24 hours at pH=8.5, temperature 26°C, and rotation speed 800rpm. The mixture was washed with deionized water for multiple times to remove unreacted dopamine and unstable polydopamine on the surface, thereby obtaining an intermediate.
[0175] The intermediate was dispersed in 200 mL of polyethyleneimine aqueous solution (mass fraction of 0.5%, mass ratio of bacterial cellulose to polyethyleneimine of 1:1), stirred continuously for 12 h at a temperature of 50°C and a rotation speed of 800 rpm, and washed with deionized water for multiple times to remove unreacted polyethyleneimine to obtain a toughening agent.
[0176] (2) Preparation of positive electrode sheet:
[0177] Polyethylene terephthalate (PET) and a toughening agent were mixed at a mass ratio of 100:2, melt blended at 300°C for 4 hours, and hot calendered after being evenly mixed. The polymer resin formed a polymer base film, and the toughening agent was dispersed in the polymer base film to form a 6 μm thick support layer.
[0178] The support layer was transferred to the reaction chamber of magnetron sputtering and vacuumed to 6×10 -5 Pa, argon gas is introduced at a flow rate of 40sccm, and plasma etching is performed under the conditions of a working gas pressure of 0.2Pa and a working power of 40W to improve the surface roughness of the supporting layer; then argon gas is introduced at a flow rate of 80sccm, and DC magnetron sputtering coating is performed under the conditions of a sputtering gas pressure of 2Pa and a sputtering power of 150W to form a 1μm thick Al layer as a conductive layer.
[0179] The MAX precursor Ti3AlC2 was etched using an etching solution containing LiF and HCl to obtain the MXene material Ti3C2T x ; The conductive agent (Ti3C2T x ), a dispersant (PVP), a first binder (CMC and SBR in a mass ratio of 1:1) and deionized water in a mass ratio of 18:2:8:72 to prepare a primer slurry, which is then coated on the surface of the conductive layer and vacuum dried at 60°C for 72 hours to form a 1µm thick primer layer, thereby obtaining a functional composite current collector A.
[0180] CuF2 and Ketjen black were mixed evenly in a mass ratio of 8:2, and high-energy ball milling was performed at 600 rpm for 5 hours to obtain positive electrode active materials; the positive electrode active materials, conductive agent SP, and binder PVDF were dispersed in solvent NMP in a mass ratio of 80:10:10, and positive electrode slurry was obtained after homogenization; the positive electrode slurry was coated on the base coating of the functional composite current collector A, and the positive electrode sheet was obtained after drying, rolling and cutting.
[0181] (3) Preparation of negative electrode sheet:
[0182] Polypropylene (PP) and toughening agent were mixed in a mass ratio of 100:2, melt blended at 180°C for 4 hours, and hot calendered after being evenly mixed. The polymer resin formed a polymer base film, and the toughening agent was dispersed in the polymer base film to form a 6 μm thick support layer.
[0183] The support layer was transferred to the reaction chamber of magnetron sputtering and vacuumed to 6×10 -5 Pa, argon gas is introduced at a flow rate of 40 sccm, and plasma etching is performed under the conditions of a working gas pressure of 0.2 Pa and a working power of 40 W to improve the surface roughness of the supporting layer; then argon gas is introduced at a flow rate of 60 sccm, and DC magnetron sputtering coating is performed under the conditions of a sputtering gas pressure of 1.5 Pa and a sputtering power of 180 W to form a 1 μm thick Cu layer as a conductive layer.
[0184] The MAX precursor Ti3AlC2 was etched using an etching solution containing LiF and HCl to obtain the MXene material Ti3C2T x ; The conductive agent (Ti3C2T x ), dispersant (PVP), first binder (PVDF) and NMP in a mass ratio of 18:2:10:70 to prepare a primer slurry, which is then coated on the surface of the conductive layer and vacuum dried at 60°C for 72h to form a 1µm thick primer layer, thereby obtaining a functional composite current collector B.
[0185] Pb and β-PbF2 are mixed evenly in a mass ratio of 65:15 to obtain a negative electrode active material; the negative electrode active material and the conductive agent CNF are mixed in a mass ratio of 80:10:10 until the color is uniform, and then a binder PTFE is added, and dry mixing is performed at 80°C for 2 hours to obtain a negative electrode powder; the negative electrode powder is hot pressed on the base coating of the functional composite current collector B, and after drying, rolling and cutting, a negative electrode sheet is obtained.
[0186] (4) Preparation of isolation film:
[0187] According to the mass ratio of 2.2:1, the phase change material No. 95 paraffin is heated to melt at 100°C, and then the flame retardant 3-thiophene boric acid (TB) with a particle size of 200nm is impregnated into the molten phase change material, so that the phase change material is coated on the surface of the flame retardant, cooled, solidified, and crushed to obtain microcapsules; the microcapsules and the second binder PVDF are added to DMF at a mass ratio of 95:5 to obtain a second safety slurry; the second safety slurry is coated on both surfaces of a 12µm thick PI base film by extrusion coating, and dried in a vacuum oven at 60°C for 24h to form a 1µm thick second safety coating, thereby obtaining a 14µm thick isolation film.
[0188] (5) Assembling fluoride ion batteries:
[0189] In a glove box (Ar atmosphere, water and O2 content <0.1ppm), the positive electrode, separator and negative electrode were encapsulated with aluminum plastic film and injected with electrolyte to make a fluoride ion battery. The electrolyte included 0.5 mol / L CsF and an organic solvent (BA and DMAc in a volume ratio of 1:1).
[0190] Embodiments 2 to 10
[0191] Please refer to Table 1. Examples 2 to 10 are basically the same as Example 1, except that the differences are as follows:
[0192] Example 2: The mass ratio of the polymer base film to the toughening agent is 100:5.
[0193] Example 3: The mass ratio of the polymer base film to the toughening agent is 100:10.
[0194] Example 4: The conductive agent of the base coating layer is carboxylated carbon nanotubes, and the carboxyl content is 6.52%.
[0195] Example 5: The conductive agent of the base coating is polyhydroxy fullerene, and the hydroxyl content is 39.1%;
[0196] Example 6: In the primer slurry, the mass fraction of the conductive agent is 12%;
[0197] Example 7: In the primer slurry, the mass fraction of the conductive agent is 6%;
[0198] Example 8: A first safety coating is also provided between the supporting layer and the conductive layer. The preparation method of the first safety coating is as follows: the phase change material chlorinated paraffin and the second binder PVDF are evenly mixed in a mass ratio of 95:5 and added to DMF to obtain a first safety slurry; the first safety slurry is coated on the surface of the supporting layer by extrusion coating, and dried in a vacuum oven at 60°C for 24 hours to form a first safety coating with a thickness of 1µm, and then a conductive layer and a primer layer are sequentially formed on the surface of the first safety coating according to Example 1.
[0199] Embodiment 9: In the second safety coating of the isolation film, the flame retardant is pentafluoroethoxy cyclotriphosphazene (FPN).
[0200] Example 10: The isolation film is not provided with a second safety coating.
[0201] Comparative Examples 1 to 4
[0202] Please refer to Table 1, Comparative Examples 1 to 4 are basically the same as Example 1, and the differences are as follows:
[0203] Comparative Example 1: No toughening agent is added to the support layer; no primer layer is provided on the surface of the conductive layer.
[0204] Comparative Example 2: No toughening agent was added to the support layer.
[0205] Comparative Example 3: No primer layer is provided on the surface of the conductive layer.
[0206] Comparative Example 4: The conductive agent of the undercoat layer is conductive carbon black SP.
[0207] The differences between Examples 2 to 8 and Comparative Examples 1 to 4 are shown in Table 1 below:
[0208] Table 1. Related parameters of functional composite current collector and isolation membrane
[0209]
[0210] Test Case
[0211] The following tests were performed on each embodiment and each comparative example:
[0212] (1) Surface roughness of the base coating: The base coating was scanned using the non-contact mode of an atomic force microscope (AFM) to test the surface roughness.
[0213] (2) Tensile strength of functional composite current collector: Cut three sample strips with a length and width of 150 mm × 15 mm, ensure that the samples are placed vertically on the test clamp of the tensile testing machine, set the test parameters and start the test, and record the tensile strength.
[0214] (3) Peel strength of positive electrode sheet: Attach the tape flatly to the steel plate, fix the sample on the tape, attach the auxiliary tape to the surface of the sample, fix the steel plate and the auxiliary tape on the constant speed tensile machine to start the test, and record the peel strength of each sample.
[0215] (4) Lithium-to-Drag Ratio of the Battery: After the battery is fully charged, its internal resistance values R1 and R2 are tested at 25°C and 120°C respectively, and the Lithium-to-Drag Ratio of the battery is calculated based on R2 / R1.
[0216] (5) Room temperature cycle test: The battery was subjected to a room temperature cycle test at 0.1C / 0.1C, and the first discharge specific capacity of the battery at 0.1C and the number of cycles at which the capacity decayed to 80% were recorded.
[0217] The above test results are shown in Table 2.
[0218] Table 2. Test results of functional composite current collector and fluoride ion battery
[0219]
[0220] As shown in Table 2, in Examples 1 to 10, the surface roughness of the primer layer is 0.3 μm to 0.7 μm, and its high surface roughness is conducive to enhancing the adhesion between the functional composite current collector and the active layer, thereby improving the peel strength of the pole piece. For the positive pole piece, the tensile strength of the functional composite current collector A reaches 183 MPa to 194 MPa, and the peel strength of the pole piece reaches 3.8 N / 25 mm to 4.4 N / 25 mm; for the negative pole piece, the tensile strength of the functional composite current collector B reaches 207 MPa to 215 MPa, and the peel strength of the pole piece reaches 4.8 N / 25 mm to 5.6 N / 25 mm, which has the advantages of high tensile strength and high peel strength.
[0221] After being assembled into a battery, the number of cycles for the batteries of Examples 1 to 10 to decay to 80% of their capacity at 0.1C is between 35 and 59 times, which is significantly higher than the number of cycles of the batteries of Comparative Examples 1 to 4, indicating that the batteries of Examples 1 to 10 have the advantage of good cycle performance after adopting the functional composite current collector provided by the present application. At the same time, a second safety coating is provided in the isolation membrane of Examples 1 to 9, and the resulting battery has a rise-to-resistance ratio of 9.8 to 286.9 when heated from 25°C to 120°C, proving that its internal resistance of the battery cell at high temperature (above the phase change temperature) is significantly increased, and abnormal loop current can be suppressed, effectively reducing the probability of thermal runaway of the battery at high temperature. In addition, in the battery of Example 8, not only is the isolation membrane provided with a second safety coating, but the functional composite current collector is also provided with a first safety coating, and its rise-to-resistance ratio is greatly improved, and the safety performance is particularly significant.
[0222] Compared with Example 1, Examples 2-3 increased the amount of toughening agent in the support layer, but the toughening effect did not improve. This may be because after the amount of toughening agent added increased, the dispersion of the toughening agent became worse, and the nanofibers were prone to agglomeration, resulting in a worse toughening effect, which reduced the tensile strength of the functional composite current collector and the peel strength of the pole piece, thereby reducing the cycle performance of the battery.
[0223] The primer layer of Example 4 uses carboxylated carbon nanotubes (carboxyl content is 6.52%) as the conductive agent, and the primer layer of Example 5 uses polyhydroxyfullerene (hydroxyl content is 39.1%) as the conductive agent. The roughness of the primer layer, the tensile strength of the functional composite current collector and the peel strength of the pole piece do not change significantly, the lift-to-drag ratio of the battery is slightly reduced, and the cycle performance is significantly improved; Examples 6 to 7 reduce the amount of MXene material in the primer layer, so that the surface roughness of the primer layer and the peel strength of the pole piece are reduced, but the safety performance of the battery is increased and the cycle performance is reduced.
[0224] In Example 8, a first safety coating is arranged between the support layer and the conductive layer, so that the safety performance of the battery is significantly enhanced and the cycle performance is also improved; in the second safety coating of the isolation membrane of Example 9, the flame retardant in the microcapsule is different from that in Example 1, and the safety performance and cycle performance of the battery are slightly reduced; the isolation membrane of Example 10 is not provided with a second safety coating, the safety performance of the battery is poor, and the cycle performance is slightly reduced.
[0225] In Comparative Example 1, no toughening agent is added to the support layer, and no primer is set on the surface of the conductive layer. The tensile strength of the functional composite current collector and the peeling strength of the pole piece are significantly deteriorated, and the cycle performance of the battery is greatly reduced; in Comparative Example 2, no toughening agent is added to the support layer, the tensile strength of the functional composite current collector is significantly deteriorated, and the cycle performance of the battery is reduced; in Comparative Example 3, no primer is set on the surface of the conductive layer, the peeling strength of the pole piece is significantly deteriorated, and the cycle performance of the battery is greatly reduced; in Comparative Example 4, the conductive agent of the primer is conductive carbon black SP, the surface roughness of the primer and the peeling strength of the pole piece are reduced, and the cycle performance of the battery is also greatly reduced.
[0226] In summary, the functional composite current collector provided by the present application adds a conductive agent with a negative charge on the surface to the bottom coating, and has a high surface roughness and good bonding performance. It can reduce the probability of fluoride ions migrating to the interface of the functional composite current collector and the active material layer and reacting through electrostatic repulsion, thereby improving the adhesion between the active material layer and the functional composite current collector and improving the cycle performance of the fluoride ion battery. At the same time, adding a toughening agent to the supporting layer of the functional composite current collector can enhance the mechanical strength of the functional composite current collector, thereby improving the cycle performance of the battery. In addition, a first safety coating is provided in the functional composite current collector, and / or a second safety coating is provided in the isolation film, which can increase the resistance of the battery at high temperature and reduce the probability of thermal runaway of the battery, thereby greatly improving the safety performance of the battery.
[0227] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0228] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.
Claims
1. A functional composite current collector, characterized in that: The invention comprises a supporting layer, a conductive layer disposed on at least one surface of the supporting layer, and a primer layer disposed on a surface of the conductive layer away from the supporting layer; The support layer includes a polymer base film and a toughening agent dispersed in the polymer base film; The primer layer includes a first binder and a conductive agent dispersed in the first binder, the functional groups on the surface of the conductive agent carry negative charges in the solution, and the functional groups include one or more of hydroxyl, carboxyl, halogen and oxygen-metal bond.
2. The functional composite current collector according to claim 1, characterized in that: The conductive agent includes one or more of carboxylated carbon nanotubes, polyhydroxy fullerenes and MXene materials; the MXene material includes Ti3C2T x 、Ti2CT x 、Ti3CNT x 、Ta4C3T x 、V2CT x 、V3C2T x 、Mo2CT x and Mo2TiC2T x One or more of, wherein T includes one or more of -OH, -F and -O, and x>0.
3. The functional composite current collector according to claim 2, characterized in that: The primer layer satisfies at least one of the following conditions: (1) The first binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, hydrogenated nitrile rubber, polyvinyl alcohol, polymethacrylic acid, polymethyl methacrylate, polyacrylic acid, sodium polyacrylate, polyacrylamide, sodium alginate, sodium carboxymethyl cellulose and carboxymethyl chitosan; (2) The mass ratio of the first binder to the conductive agent is 1:(0.1-4); (3) The base coating layer further includes a dispersant, and the dispersant includes one or more of polyvinyl pyrrolidone, sodium polyacrylate, sodium lignin sulfonate and sodium polystyrene sulfonate, and the mass ratio of the first binder to the dispersant is 1: (0.1~1); (4) The thickness of the primer layer is 0.5 μm to 3 μm; (5) The surface roughness of the primer layer is 100 nm to 800 nm; (6) The peel strength of the primer layer is 14N / 25mm~30N / 25mm.
4. The functional composite current collector according to any one of claims 1 to 3, characterized in that: The toughening agent comprises bacterial cellulose, a polydopamine layer coated on the bacterial cellulose and an amino modified layer grafted on the polydopamine layer.
5. The functional composite current collector according to claim 4, characterized in that: The preparation method of the toughening agent comprises the following steps: mixing bacterial cellulose, dopamine and a buffer solution, allowing the dopamine to self-polymerize to form a polydopamine layer covering the bacterial cellulose, to obtain an intermediate; The intermediate is dispersed in a mixed solution containing an aminating agent, and the aminating agent is grafted onto the polydopamine layer to form the amino-modified layer, thereby obtaining the toughening agent.
6. The functional composite current collector according to claim 5, characterized in that: At least one of the following conditions is met: (1) The mass ratio of the bacterial cellulose, the dopamine and the amination agent is 1: (0.5-2): (0.5-5); (2) The bacterial cellulose has a diameter of 10 nm to 200 nm, a length of 100 nm to 2000 nm, and an aspect ratio of 0.5 to 200; (3) the amination agent includes one or more of ethylenediamine, histamine, polyethyleneimine and hexadecyltrimethylammonium bromide; (4) The mass ratio of the polymer base film to the toughening agent is 100:(1-10); (5) The thickness of the support layer is 4 μm to 8 μm.
7. The functional composite current collector according to any one of claims 1 to 3, characterized in that: The functional composite current collector further comprises a first safety coating, wherein the first safety coating is disposed between the support layer and the conductive layer; The first safety coating comprises a second binder and a phase change material in a mass ratio of (2-5):(95-98), wherein the melting point of the phase change material is 85°C-120°C; or The first safety coating includes a second binder and microcapsules in a mass ratio of (2~10):(90~98), the microcapsules include a flame retardant and a phase change material coated on the flame retardant, the mass ratio of the flame retardant to the phase change material is 1:(1.2~40), and the melting point of the phase change material is 85℃~120℃.
8. A method for preparing a functional composite current collector according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polymer resin and the toughening agent are melt-blended and the obtained mixture is subjected to film-forming treatment, wherein the polymer resin forms a polymer base film and the toughening agent is dispersed in the polymer base film to obtain a support layer; forming a conductive layer on at least one surface of the support layer; A primer slurry containing a first binder and a conductive agent is applied onto the conductive layer and dried to form a primer layer.
9. A fluoride ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the positive electrode sheet and / or the negative electrode sheet comprises the functional composite current collector as described in any one of claims 1 to 7, or comprises a functional composite current collector prepared by the preparation method of the functional composite current collector as described in claim 8.
10. The fluoride ion battery according to claim 9, characterized in that: The isolation film includes a base film and a second safety coating coated on at least one surface of the base film; The second safety coating comprises a second binder and a phase change material in a mass ratio of (2-5):(95-98), wherein the melting point of the phase change material is 85°C-120°C; or The second safety coating includes a second binder and microcapsules in a mass ratio of (2~10):(90~98), the microcapsules include a flame retardant and a phase change material coated on the flame retardant, the mass ratio of the flame retardant to the phase change material is 1:(1.2~40), and the melting point of the phase change material is 85℃~120℃.
Citation Information
Patent Citations
Collector used for negative pole of lithium ion battery
CN102034981A
Electrode pole sheet and electrochemical device
CN110660957A
Polymer-based negative current collector and preparation method thereof
CN115763696A
Conductive composite current collector, preparation method thereof and battery
CN119581570A
Current collector provided with undercoat layer, electrode, and non-aqueous electrolyte secondary battery
JP2019036490A
Cited By
Design method of high-entropy MXene-high-viscosity colloid composite coating battery diaphragm
CN120300403A
Current collector, method for preparing current collector, pole piece, lithium ion battery and electric device
CN120376659A